Multilevel Analysis of Nurse’s Performance Predictors at Dr. Moewardi Hospital, Surakarta - Mardiah, Adriana; Tamtomo, Didik; Murti, Bhisma (Journal of Health Policy and Management, 2025)
Background: Nurse Performance plays a role as a determinant of patient satisfaction when providing nursing care. Nursing services in hospitals are one of the determining factors for good or bad service, quality and image of a hospital. Factors that influence nurse performance are gender, working time arrangements, education, work experience and job satisfaction. The aim of this study was to analyze the performance of inpatient and outpatient ward nurses at Dr. Moewardi Hospital. Subject and Method: This research uses an observational analytic design with a cross-sectional approach. This research is intended to find the relationship between the independent variables, namely gender, working time arrangements, education, work experience and job satisfaction, with the dependent variable, namely the performance of nurses in the inpatient and outpatient wards at Dr. Moewardi. This research was conducted in October-November 2023. A sample of 200 posyandu cadres was selected using random sampling. Data collection was carried out using questionnaires/interviews and data was analyzed using a multiple linear regression analysis model with a multilevel approach. Results: Gender has an influence and is significant between gender and nurse performance (b = -1.79; 95% CI = -3.13 to -0.45; p = 0.009). Working time arrangements have an influence on nurse performance, and this influence is statistically significant (b = 1.96: 95% CI = 0.39 to 3.54; p = 0.014). Job satisfaction has a positive and significant influence on nurse performance (b = 0.32 CI 95% = 0.10 to 0.4). The results of education and work experience did not show a statistically significant difference in nursing performance between nurses with DIII education and the nursing profession (b = 0.32; 95% CI = -0.86 to 1.51) and work experience of more than 12 years and less than 12 years (b = 0.71; 95% CI = -0.75 to 2.17). The results of this multilevel analysis also found that there was a contextual influence of the ward on nurse performance (ICC= 15.09%). Conclusion: Nurse performance is directly influenced by gender, working time arrangements and job satisfaction. Variations at level 2 wards have a contextual influence on nurse performance.